PEMBELAJARAN PASSING BAWAH BOLA VOLI MINI DENGAN PENDEKATAN BERMAIN SDN 12 KELEPUK KABUPATEN LANDAK - Kimhin, Kimhin; Simanjuntak, Victor; Triansyah, Andika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrakThe problem of this study is that students learn passing under a mini volleyball, as when learning passing under volleyball it is difficult not to have the right approach, lack of means at the time of learning volleyball when the students do not notice it, the need for new innovations for children educate to learn passing down easily, with the approach of playing the students are more controlled and the students prefer and want to do passing down.This classroom action research is carried out with the aim as a solution to maximize the learning activities of the students, especially the basic bottom passing technique to find out the increase of passing under the mini volley with the approach of play, to improve the result of lower passing learning which is indicated by test result, learning result passing under volley mini and good student behavior test results. The method used is descriptive method with type of class action research (PTK). Subjects in the study were 28 students. The success of students while learning passing under the volleyball certainly can not be obtained very easily, it needs an interesting innovation and the right teaching materials so that the learning outcomes increase and maximize. The result of the research has a positive impact that is shown by the increase of the result of the complete cycle I totaled 14 or 50% unfinished amounting to 14 or 50% cycle II is completely categorized all (total 28 students) 100% complete all. Keywords: Learning, Passing down, Mini Volleyball, Aproach to Play